2012
DOI: 10.2478/v10249-012-0047-y
|View full text |Cite
|
Sign up to set email alerts
|

Lisinopril-Induced Pemphigus Foliaceus in a Patient with Diabetes Mellitus and Kaposi-Juliusberg Varicelliform Eruption

Abstract: Drugs have often been implicated as the cause of pemphigus. Lisinopril is a drug of the angiotensin-converting enzyme inhibitor class primarily used in the treatment of hypertension, congestive heart failure, heart attacks, and also in preventing renal and retinal complications of diabetes mellitus. Various side-effects have been described in the English medical literature related to lisinopril, but only one case with pemphigus foliaceus as an adverse reaction to lisinopril. To the best of our knowledge, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Thus, given the temporal association between the patient's isolated Lisinopril dose escalation and her skin eruptions 2 months later, a drug‐induced adverse reaction was entertained. Particularly, drug‐induced pemphigus foliaceus (PF), another autoimmune blistering skin disorder, was highly suspected, given its previous reporting twice within the literature in association with Lisinopril use , along with the flaccid, eroded and crusted nature of our patient's skin lesions and their mucous‐sparing distribution .…”
Section: Case Presentationmentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, given the temporal association between the patient's isolated Lisinopril dose escalation and her skin eruptions 2 months later, a drug‐induced adverse reaction was entertained. Particularly, drug‐induced pemphigus foliaceus (PF), another autoimmune blistering skin disorder, was highly suspected, given its previous reporting twice within the literature in association with Lisinopril use , along with the flaccid, eroded and crusted nature of our patient's skin lesions and their mucous‐sparing distribution .…”
Section: Case Presentationmentioning
confidence: 89%
“…Two mechanisms have been suggested to date on how ACEIs may induce BP: first, through activating and/or potentiating the pro‐inflammatory kinin system via inhibiting the system's inactivating angiotensin‐converting enzyme (ACE) and second, through their hapten‐like properties of binding to and modifying lamina lucida proteins, thereby triggering the production of autoantibodies against those ‘neo‐antigens’ . However, the latter mechanism has been previously often more accredited, owing to Lisinopril's intrinsic amide group which has been shown to exhibit acantholysis‐triggering properties in vitro . This may potentiate BP development in already predisposed individuals such as elderly patients, who undergo a dose escalation of their Lisinopril, such as the case of our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Thiol-mediated cell-cell adhesion loss seem to be caused by direct biochemical aberration of desmosome structure itself, e.g. by inhibition of keratinocyte transglutaminase or acetylcholinesterase or forming thiol-cysteine bonds instead of cysteine-cysteine bonds making the protein dysfunctional [ 40 , 56 , 57 ]. However thiols also are reported to activate the proteases, and considered to bind DSGs that results in neoantigen formation that triggers the autoimmunity [ 57 ].…”
Section: Discussion Of the Issue Of Pemphigus Triggering In Relation mentioning
confidence: 99%
“…Therefore, the occurrence of cutaneous adverse events following antihypertensive therapy will tend to affect mainly middle-aged and elderly subjects with serious disease and it is necessary for the clinician to intervene promptly. These classes of drugs seem to be the most often reported antihypertensive pemphigus-associated drugs in both pemphigus vulgaris with molecules as captopril (Feng et al, 2011;Garcıa et al, 2016;Korman, Eyre, Zone, & Stanley, 1991), fosinopril (Garcıa et al, 2016) enalapril (Patsatsi et al, 2009), cilazapril (Parfrey et al, 1980), quinapril (Ong et al, 2000), benazepril (Goldberg, Shirazi, & Brenner, 2008) and Ramipril (Skandalis et al, 2012), and in pemphigus foliaceus with molecules as captopril (Blanken, Doeglas, de Jong, Kardaun, & van Leeuwen, 1988;Christeler, Waeber, Brunner, & Delacrétaz, 1982;Goldberg et al, 2008), enalapril (Bernard et al, 1985), Vukovi c, & Vesi c, 2012;Ong et al, 2000), cilazapril (Thami et al, 2001), lisinopril (Korman et al, 1991), ramipril (Stavropoulos et al, 2003). The first report on pemphigus induced by an antihypertensive (captopril) is dated 1980 (Goldberg et al, 2005) and from that date a large number of other antihypertensives has been reported to cause pemphigus (Brenner & Goldberg, 2011;Ruocco et al, 1993;Ruocco & Sacerdoti, 1991).…”
Section: Other Non-thiol Non-amide Non-phenolic Drugsmentioning
confidence: 99%